Factors affecting online purchase intention: the case of e-commerce on lazada - Le-Hoang, Phuong Viet (2020)
This study aims to explore the scale and measure of the impact of factors affecting theonline shopping intention of the consumer on the Lazada e-commerce website in Ho Chi Minh City. The study confirms the theoretical analysis of consumer behavior (Theory of Reasoned Action - TRA), (Theory of Planned Behavior – TPB), as well as compares the research articles related to online shopping intention of domestic and foreign authors. From the survey results from 300 customers, the author pointed out that six factors positively affecting online purchase intention include usefulness - convenience, trust, behavior control awareness, business competency, and reference group opinion. The other factor is the perceived risk that has negative affect customers' online shopping intentions. Since then, the research offers the causes, solutions, implications to help traders on e-commerce sites capture the needs and psychology of customers and help them partially improve their ability to attract customers online shopping in Ho Chi Minh City.